Developmental regression associated with PTSD in children: a poorly defined and understudied phenomenon - Alameddine Abbas (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology)
Developmental regression (DR) is a clinically relevant phenomenon that is most recognized in neurodevelopmental disorders such as in autism spectrum disorder, but it is also described in association with psychological trauma and post-traumatic stress disorder (PTSD) in children. It is not uncommon for children with PTSD to present symptoms of DR, which manifests as a loss of recently acquired developmental skills such as toilet training or language skills. International diagnostic classifications are not consistent regarding DR nosology. There exists, however, some theoretical ground to group DR with the cluster of dissociative symptoms in PTSD. There is no agreement on how to define, classify and manage DR in PTSD due to a research gap, which require further studies.